Development guide assessments of the content of foods and beverages and the accounting of individual energy need - Syabaniyah, Nuranisa; Rhenadia, Annisa; Novitasari, Mariska Diah; Suryanda, Ade (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Sukabumi, 2022)
The study aims to develop and validate the biology practical guide on fast food and beverage content tests and energy accounting for individual amounts. These practical guidelines require learners to do a high-quality test on processed or ready-to-eat food and beverage. The research and developmet) with the 4-d (four-d models) development model by Thiagarajan (1974). The study was carried out on 03-04 December 2021. The practical guide has been validated by two experts. The first validator was a master's degree in biology. Whereas, the second validator is a master graduate at biomedical. The results of the development of the preview guide for food testing materials get valididtas' value on a nimble feature of 4.6, a display aspect of 3.8, and a 3.6 presentation aspect. Aspects of language fall into a very valid category, while for aspects of view and presentation go into valid categories. Thus, the guide to this practice is worthy to be used as a learning tool in the xi high school food test material. Key words: development, food content test, calculation of the amount of energy, practical guide, validation